The motivation code : discover the hidden forces that drive your best work - Henry, Todd; Penner, Rod; Hall, Todd W. (Portfolio, 2020)
"From the author of Die Empty and The Accidental Creative, a new framework for understanding what motivates us and why. What drives us to unleash our best work? And how do we tap into that drive to get superior results with our managers, coworkers, and direct reports? As Todd Henry reveals in this illuminating book, drawing on decades of research and interviews with over 100,000 people, the answer is not one size fits all: some people are energized by a race against the clock, while others put in extra effort only when they feel part of a team. For still others, nothing is as motivating as the possibility of public recognition. Henry shows, in fact, that there are twenty-seven "motivational themes", each with its own unique DNA. For instance: · Those driven to Achieve Potential strive to build an ideal future, even when others may not see as far ahead. · Those needing to Overcome must conquer whatever obstacles come their way, no matter how difficult or time-consuming. · Those who strive to Comprehend and Express are obsessed with mastering new skills and showing off what they know--which is often a lot. · Those who want to Make It Right thrive when systems are running smoothly and usually know the "proper way" to do things. The Motivation Code teaches us to decode our Core Motivation so that we can have conversations, make decisions, and even choose career paths that lead us to experience engagement and fulfillment. Once we know how to activate our inner drivers, we can transform the work we do into work we love"--